2016
DOI: 10.1016/j.ccell.2015.12.005
|View full text |Cite
|
Sign up to set email alerts
|

MiR-215 Is Induced Post-transcriptionally via HIF-Drosha Complex and Mediates Glioma-Initiating Cell Adaptation to Hypoxia by Targeting KDM1B

Abstract: SUMMARY The hypoxic tumor microenvironment serves as a niche for maintaining the glioma-initiating cells (GICs) that are critical for glioblastoma (GBM) occurrence and recurrence. Here we report that hypoxia-induced miR-215 is vital for reprograming GICs to fit the hypoxic microenvironment via suppressing the expression of an epigenetic regulator KDM1B and modulating activities of multiple pathways. Interestingly, biogenesis of miR-215 and several miRNAs is accelerated post-transcriptionally by hypoxia-inducib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
65
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(71 citation statements)
references
References 48 publications
2
65
0
2
Order By: Relevance
“…Nowadays many new therapies for glioma such as immunotherapy and gene therapy are constantly emerging, which are expected to further improve the prognosis of patients with glioma (Jiang et al, 2015). CD164 is a sialic acid mucin located on the No.6 chromosome (Hu et al, 2016).Studies have shown that CD164 played a role in regulating the growth, apoptosis and invasive behavior of solid tumors such as colon cancer, cervical cancer and medulloblastoma (Forde et al, 2007) ; (Shi et al, 2014). The research results showed that CD164 can be used as a molecular biological marker for acute lymphoblastic leukemia (Coustan-Smith et al, 2011).…”
Section: Introductionmentioning
confidence: 82%
“…Nowadays many new therapies for glioma such as immunotherapy and gene therapy are constantly emerging, which are expected to further improve the prognosis of patients with glioma (Jiang et al, 2015). CD164 is a sialic acid mucin located on the No.6 chromosome (Hu et al, 2016).Studies have shown that CD164 played a role in regulating the growth, apoptosis and invasive behavior of solid tumors such as colon cancer, cervical cancer and medulloblastoma (Forde et al, 2007) ; (Shi et al, 2014). The research results showed that CD164 can be used as a molecular biological marker for acute lymphoblastic leukemia (Coustan-Smith et al, 2011).…”
Section: Introductionmentioning
confidence: 82%
“…Nowadays many new therapies for glioma such as immunotherapy and gene therapy are constantly emerging, which are expected to further improve the prognosis of patients with glioma (Jiang et al, 2015). CD164 is a sialic acid mucin located on the No.6 chromosome (Hu et al, 2016).Studies have shown that CD164 played a role in regulating the growth, apoptosis and invasive behavior of solid tumors such as colon cancer, cervical cancer and medulloblastoma (Forde et al, 2007) ; (Shi et al, 2014). The research results showed that CD164 can be used as a molecular biological marker for acute lymphoblastic leukemia (Coustan-Smith et al, 2011).…”
Section: Introductionmentioning
confidence: 82%
“…Среди мишеней miR-215 в ОСК глиобластомы имеется мРНК KDM1B (lysine demethylase 1B) из семейства JMJC [85]. Следует отметить, что гистоновые деметилазы JMJC могут быть другой патогенетически значимой мишенью (R)-2HG: in vitro 2-гидроксиглутарат блокирует многие 2-оксоглутарат-зависимые ферменты, в том числе гистоновые деметилазы KDM2A, KDM4A, KDM4C, KDM7A [74].…”
Section: (рис 2)unclassified
“…Нокдаун KDM1B усиливал формирование нейросфер, экспрессию генов, ассоциированных с метаболизмом глюкозы, в субпопуляции ОСК; сниженная экспрессия KDM1B в тканях глиобластомы пациентов коррелировала с увеличенной экспрессией HIF1A и miR-215 и с неблагоприятным прогнозом. HIF1a, уровень которого увеличивается при гипоксии в ОСК глиобластомы, взаимодействует с Drosha-комплексом pri-miR-215, а сайленсинг HIF1a предотвращает гипоксия-индуцированное увеличение экспрессии miR-215 [85]. Другая деметилаза -KDM1A (lysine demethylase 1A) -является прямой мишенью miR-329 при нейробластоме; при этом уровень этой опухоль-супрессорной miR-329 понижается при нейробластоме [86].…”
Section: (рис 2)unclassified